Interferensi bahasa Indonesia terhadap bahasa Sunda dalam karangan berbahasa Sunda siswa SMP - Rusyana, Enang; Rohmah, Raden Utami Nur (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
The number of Sundanese language speakers is 34 million, according to the 2020 census by BPS. However, many young urban Sundanese do not speak Sundanese. Salminen and UNESCO say the language situation is considered vulnerable and endangered. Meanwhile, the Ministry of Education, Culture, Research, and Technology (Kemdikbudristek) states that the vitality of the Sundanese language is safe. This research aims to describe the interference of the Indonesian language on Sundanese language writing in compositions of the young Sundanese generation. Interference is one of the characteristics of language users' poor understanding of the language they use. The high level of Indonesian language interference in Sundanese student compositions shows that students have a poor understanding of Sundanese. The study uses a qualitative descriptive method. Analysis was conducted using Sundanese letters, words, and sentences based on the theory and Sundanese language dictionary. The study results show that Indonesian language interference in Sundanese student compositions occurs in phonology, morphology, and syntax with low categories. It indicates that the Sundanese language skills of the young generation in Bandung are good. Therefore, the vitality of the Sundanese language is still considered safe according to the Ministry's decision.